ANALISIS PENGARUH EFEKTIVITAS IKLAN DAN WORD OF MOUTH TERHADAP BRAND AWARENESS, DAN NILAI PELANGGAN SERTA DAMPAKNYA TERHADAP MINAT BELI HAND AND BODY LOTION MARINA (Studi Kasus Pada Masyarakat di Kota Semarang) - Permana, Panji; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2015)
This study aims to examine and analyze the effect of the effectiveness of advertising and word of mouth on brand awareness, then examine and analyze the effect of brand awareness and customer value on purchase intention of the Marina hand and body lotion product.Â Â  The sample in this study were 200 respondents that came from the people in the city of Semarang which recognize Marina hand and body lotion products. The method used is purposive sampling. Analyzer used in this study is Structural Equation Modeling (SEM) which is operated through a program AMOS 20.0The result showed that the effectiveness of advertising and word of mouth has positive and significant effect on brand awareness. Then, brand awareness and customer value has positive and significant effect on purchase intention.